Elevation of Circulating miR-210-3p in High-Altitude Hypoxic Environment - Yan, Yan; Wang, Cheng; Zhou, Wanqing; Shi, Yonghui; Guo, Pengtao; Liu, Yuxiu; Wang, Junjun; Zhang, Chen-Yu; Zhang, Chunni (Frontiers in Physiology, 2016)
Background: The induction of miR-210-3p, a master hypoxamir, is a consistent feature of the hypoxic response in both normal and malignant cells. However, whether miR-210-3p acts as a circulating factor in response to a hypoxic environment remains unknown. The current study aimed to examine the effect of a high-altitude hypoxic environment on circulating miR-210-3p. Methods: We examined and compared the levels of miR-210-3p using TaqMan-based qRT-PCR in both peripheral blood cells and plasma from 84 ethnic Chinese Tibetans residing at 3560 m, 46 newly arrived migrant Han Chinese (Tibet Han) and 82 Han Chinese residing at 8.9 m (Nanjing Han). Furthermore, we analyzed the correlations of miR-210-3p with hematological indices. Results: The relative concentrations of miR-210-3p to internal reference U6 in blood cells were significantly higher in the Tibet Han group (1.01±0.11, P<0.001) and in the Tibetan group (1.17±0.09, P<0.001) than in the Nanjing Han group (0.51±0.04). The absolute concentrations of plasma miR-210-3p were also markedly elevated in the Tibet Han group (503.54±42.95 fmol/L, P=0.004) and in the Tibetan group (557.78±39.84 fmol/L, P<0.001) compared to the Nanjing Han group (358.39±16.16 fmol/L). However, in both blood cells and plasma, miR-210-3p levels were not significantly different between the Tibet Han group and the Tibetan group (P=0.280, P=0.620, respectively). Plasma miR-210-3p concentrations were positively correlated with miR-210-3p levels in blood cells (r=0.192, P=0.005). Furthermore, miR-210-3p levels in both blood cells and plasma showed strong positive correlations with red blood cell counts and hemoglobin and hematocrit values. Conclusion: These data demonstrated, for the first time, that miR-210-3p might act as a circulating factor in response to hypoxic environments and could be associated with human adaptation to life at high altitudes.